2013
DOI: 10.1098/rsbl.2013.0154
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of parental care under the risk of predation: how much should parents reduce care?

Abstract: Predation can be an important agent of natural selection shaping parental care behaviours, and can also favour behavioural plasticity. Parent birds often decrease the rate that they visit the nest to provision offspring when perceived risk is high. Yet, the plasticity of such responses may differ among species as a function of either their relative risk of predation, or the mean rate of provisioning. Here, we report parental provisioning responses to experimental increases in the perceived risk of predation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 17 publications
3
105
1
Order By: Relevance
“…This agrees with previous studies on the topic (e.g. Eggers et al 2005Eggers et al , 2008Massaro et al 2008;Peluc et al 2008;Zanette et al 2011;Ghalambor et al 2013;Hua et al 2014) and also with the reduction in nest visits observed for female Blackbirds during the incubation stage (Ibáñez-Á lamo and Soler 2012). However, adult Blackbirds did not show an increase in latency time due to a high perceived predation risk (prediction 1b).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This agrees with previous studies on the topic (e.g. Eggers et al 2005Eggers et al , 2008Massaro et al 2008;Peluc et al 2008;Zanette et al 2011;Ghalambor et al 2013;Hua et al 2014) and also with the reduction in nest visits observed for female Blackbirds during the incubation stage (Ibáñez-Á lamo and Soler 2012). However, adult Blackbirds did not show an increase in latency time due to a high perceived predation risk (prediction 1b).…”
Section: Discussionsupporting
confidence: 82%
“…While several studies have demonstrated a reduction in offspring provisioning rates (e.g. Eggers et al 2005Eggers et al , 2008Massaro et al 2008;Peluc et al 2008;Zanette et al 2011;Ghalambor et al 2013;Hua et al 2014;LaManna and Martin 2016), it remains unknown whether the reduction in nest visitation rates differs between sexes. Martin and Badyaev (1996) suggested that nest predation could place greater constraints on female than on male plumage brightness, implying that each sex responds differentially to nest predation risk.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence, including in threespined stickleback [22], that when predation risk is high, males decrease conspicuous courtship displays that could attract predators with benefits for both signallers and receivers [6,7,24]. There is also substantial evidence that parents decrease offspring care when predation risk is high [25]. For example, threespined stickleback fathers reduce their paternal care when presented with a predator model [26].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the consequences of predation risk, birds have evolved behavioral (Lima 1998;Conway and Martin 2000a;Ghalambor and Martin 2002;Kovarik and Pavel 2011) and physiological responses (Peluc et al 2008;Hawlena and Schmitz 2010;Travers et al 2010). Parental responses to predation pressure, such as choice of a concealed nesting site (Nilsson 1984), active and passive defence of the nest (Montgomerie and Weatherhead 1988;Eggers et al 2005), altered incubation behavior (Deeming 2002;Zanette et al 2011) and posthatching parental care (Ghalambor et al 2013) can have a strong impact on offspring fitness (Lima 2009;Nord and Nilsson 2011). However, increased energy and time investment as a result of parental responses to predation may affect life-history trade-offs and reduce the parents' future reproductive value (Angelier and Chastel 2009).…”
Section: Introductionmentioning
confidence: 99%